2021
DOI: 10.1002/smll.202101897
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing the Induction of Immunogenic Cell Death Via Artificial Engineered Cascade Bioreactor‐Enhanced Chemo‐Immunotherapy for Optimizing Cancer Immunotherapy

Abstract: Traditional chemo‐immunotherapy can elicit T cell immune response by inducing immunogenic cell death (ICD), however, insufficient ICD limits the lasting antitumor immunotherapeutic efficacy. Herein, tadpole–ovoid manganese‐doped hollow mesoporous silica coated gold nanoparticles (Au@HMnMSNs) as biodegradable catalytic cascade nanoreactors are constructed to generate intratumoral high‐toxic hydroxyl radicals combined with DOX and Aspirin (ASA) for enhancing the induction of ICD and maturation of dendritic cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…reported that 3.6 nm gold NPs (AuNPs) can catalyze glucose oxidation, giving the same products as glucose oxidase (GOx) . Since then, AuNPs have become a very popular GOx mimicking nanozyme. In that work, Comotti et al . mentioned that the surface atoms need to be considered as the nanozyme active sites, consistent with our opinion.…”
Section: Introductionmentioning
confidence: 99%
“…reported that 3.6 nm gold NPs (AuNPs) can catalyze glucose oxidation, giving the same products as glucose oxidase (GOx) . Since then, AuNPs have become a very popular GOx mimicking nanozyme. In that work, Comotti et al . mentioned that the surface atoms need to be considered as the nanozyme active sites, consistent with our opinion.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al found a method that utilized tadpole-ovoid manganese-doped hollow mesoporous silica to administer gold nanoparticles (AuNPs), DOX, and aspirin (ASA) to strengthen ICD ( Figure 7 ). 90 When the structure collapsed in an acidic and GSH-sufficient environment, AuNPs were exposed to glucose for GOx-like catalysis, and Mn 2+ was liberated for a Fenton-like reaction. ROS was then produced by the dual effects.…”
Section: Combined Therapy Targeting Glucose Metabolismmentioning
confidence: 99%
“…Aspirin (ASA) was found to improve the immune microenvironment [ 134 ] by reducing the secretion of PGE2 via inhibiting COX-2 expression. Sun et al [ 135 ] constructed the Au@HMnMSNs nanoplatform loading DOX and ASA. Nanoparticles can consume GSH in an acidic environment and release Mn 2+ to further induce Fenton-like reactions, while the inner gold nanoparticles can convert glucose into H 2 O 2 to accelerate •OH generation with inducing a starving effect.…”
Section: Comprehensive Antitumor Therapeutic System Of “Metal-oxidase” System Combined With Other Therapiesmentioning
confidence: 99%